Peluang Dan Tantangan Industri Pencetak Insan Kreatif Dan Handal Di Dunia Pertelevisian 1 - -, Handriyotopo (Seni Media Rekam ISI Surakarta, 2014)
The growth of the television industry is quite rapid and gives a significant impacton the growth of the audiovisual information media . No exception that in this industryalso demands a reliable and creative human resources in preparing and developing thecontents of the program. Qualified human resources is the key word to be prepared infacing global competition in the television media industry. The power of television isstill able to hypnotize for everyone to search for information and entertainment.Considerable opportunities of this in the end gives a pretty good chance for thosewho want to engage in the creative industry of television programs. It is not surprisingthen that many emerging courses offered employment in the industry. Not only at thelevel of vocational but also on the level of D4 and S1 program broadcasting, television,and film.Keywords: opportunities, television industry, human resources